FAK Activation Promotes SMC Dedifferentiation via Increased DNA Methylation in Contractile Genes. Issue 12 (27th October 2021) - Jeong, Kyuho; Murphy, James M.; Kim, Jung-Hyun; Campbell, Pamela Moore; Park, Hyeonsoo; Rodriguez, Yelitza A.R.; Choi, Chung-Sik; Kim, Jun-Sub; Park, Sangwon; Kim, Hyun Joon; Scammell, Jonathan G.; Weber, David S.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Vascular smooth muscle cells (SMCs) exhibit remarkable plasticity and can undergo dedifferentiation upon pathological stimuli associated with disease and interventions. Objective: Although epigenetic changes are critical in SMC phenotype switching, a fundamental regulator that governs the epigenetic machineries regulating the fate of SMC phenotype has not been elucidated. Methods and Results: Using SMCs, mouse models, and human atherosclerosis specimens, we found that FAK (focal adhesion kinase) activation elicits SMC dedifferentiation by stabilizing DNMT3A (DNA methyltransferase 3A). FAK in SMCs is activated in the cytoplasm upon serum stimulation in vitro or vessel injury and active FAK prevents DNMT3A from nuclear FAK-mediated degradation. However, pharmacological or genetic FAK catalytic inhibition forced FAK nuclear localization, which reduced DNMT3A protein via enhanced ubiquitination and proteasomal degradation. Reduced DNMT3A protein led to DNA hypomethylation in contractile gene promoters, which increased SMC contractile protein expression. RNA-sequencing identified SMC contractile genes as a foremost upregulated group by FAK inhibition from injured femoral artery samples compared with vehicle group. DNMT3A knockdown in injured arteries reduced DNA methylation and enhanced contractile gene expression supports the notion that nuclear FAK-mediated DNMT3A degradation via E3 ligase TRAF6 (TNF [tumor necrosis factor] receptor-associated factor 6) drives differentiation of SMCs. Furthermore, we observed that SMCs of human atherosclerotic lesions exhibited decreased nuclear FAK, which was associated with increased DNMT3A levels and decreased contractile gene expression. Conclusions: This study reveals that nuclear FAK induced by FAK catalytic inhibition specifically suppresses DNMT3A expression in injured vessels resulting in maintaining SMC differentiation by promoting the contractile gene expression. Thus, FAK inhibitors may provide a new treatment option to block SMC phenotypic switching during vascular remodeling and atherosclerosis.